2019
DOI: 10.1177/1078155219875797
|View full text |Cite
|
Sign up to set email alerts
|

Pazopanib-induced fatal heart failure in a patient with unresectable soft tissue sarcoma and review of literature

Abstract: Introduction Pazopanib, an oral multi-targeted tyrosine kinase inhibitor, is associated with improved outcomes in patients with unresectable or metastatic soft tissue sarcoma. Pazopanib may cause cardiotoxicity such as heart failure. Case report A 50-year-old female patient with no cardiovascular risk factors other than the previous treatment with adriamycin had a baseline left ventricular ejection fraction of 60%. She was receiving pazopanib 800 mg once daily for advanced leiomyosarcoma of the presacral area.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…This patient was able to receive three cycles of PLD prior to the cardiac event. It is uncertain if PLD was the sole contributing factor for this cardiac event, as this patient had a lower baseline LVEF of 50%-55% and was previously on pazopanib, another known agent that may cause cardiotoxicity [ 19 , 20 ]. The most common cardiotoxic agents used in the sarcoma group were pazopanib and ifosfamide.…”
Section: Discussionmentioning
confidence: 99%
“…This patient was able to receive three cycles of PLD prior to the cardiac event. It is uncertain if PLD was the sole contributing factor for this cardiac event, as this patient had a lower baseline LVEF of 50%-55% and was previously on pazopanib, another known agent that may cause cardiotoxicity [ 19 , 20 ]. The most common cardiotoxic agents used in the sarcoma group were pazopanib and ifosfamide.…”
Section: Discussionmentioning
confidence: 99%
“…Current data regarding the risk of HF occurrence following PKI exposure are sparse. Some case reports describe the relevance of pazopanib in the occurrence of HF in patients with sarcoma 11–14 . The American Heart Association classified certain PKIs according to their ability to induce or precipitate HF based on published clinical trials 17 .…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have shown an increased risk of HF in patients exposed to sunitinib and sorafenib, while some case reports describe the impact of pazopanib on HF occurrence among sarcoma patients. [11][12][13][14][15][16] In a scientific statement, the American Heart Association classified lapatinib, imatinib, sunitinib and sorafenib as carrying moderate to minor risks of HF. 17 The primary objective of the current study was to identify the PKIs most frequently associated with an HF outcome.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation